Sex and the City: Exploring Young Women's Perceptions and Experiences of Unwanted Sexual Attention in Licensed Venues - Fileborn, Bianca (Current Issues in Criminal Justice, 2012)
Recent research has highlighted the need to explore how specific social contexts influence the occurrence of sexual violence and sexually harassing behaviours. This article considers the occurrence of unwanted sexual attention towards young women within the social context of licensed venues in Melbourne, Victoria. Using focus group data from a small qualitative study, three ‘characteristics’ of unwanted sexual attention are considered: the forms this behaviour takes and how it impacts young women; the nature of the relationship between victim and perpetrator; and the role of venue culture in facilitating this behaviour. It is argued throughout this article that an intersection of broader social norms and the specific social norms and cultural mores of licensed venues creates a social environment that can facilitate the occurrence of unwanted sexual attention, and that restrains the ways in which young women are able to respond to these experiences.
Keywords: Camille

Democratising the popular: the case of pop music in France and Britain - Looseley, David L. (International Journal of Cultural Policy, 2012)
The article represents the second phase of a comparative project on French and British cultural policy. The project's guiding hypothesis is that conceptualisations of the popular have been a crucial driver of policy change in France and Britain, raising complex issues about the nature of cultural democracy. The second phase, including this article, takes pop music as a case study for that hypothesis. The article explores three major issues. It asks how and why, in their attempts to rethink cultural democracy for the twenty-first century, French and British policy agencies have recognised pop music as a ‘democratic' form worthy of state support. It critically examines some of the theoretical issues this has raised, comparing and contrasting the ways in which the two national policy sets have variously represented pop as having symbolic, economic and social meanings. And it argues that what has been less adequately addressed is its aesthetic meaning.
Publisher: Routledge _eprint: https://doi.org/10.1080/10286632.2012.718917
Keywords: France and the UK; cultural democracy; pop music

Beyond the Dance Floor: Female DJs, Technology and Electronic Dance Music Culture - Farrugia, Rebekah (Intellect Books, 2012)
A pathbreaking study of the women who create electronic dance music, Beyond the Dance Floor focuses on the largely neglected relationship between these women and the conceptions of gender and technology that continue to inform the male-dominated culture surrounding electronic music. In this volume, Rebekah Farrugia explores a number of important issues, including the politics of identity and representation, the bonds formed by women within the DJ community and the role female DJs and producers play in this dance music culture as well as in the larger public sphere. Though Farrugia primarily focuses on women's relationship to music-related technologies – including vinyl, mp3s and digital production software – she also deftly extends her argument to the strategic use of the Internet and web design skills for purposes tied to publicity, networking and music distribution.
Google-Books-ID: L7qrDwAAQBAJ
Keywords: Music / Genres & Styles / Electronic; Performing Arts / Dance / General; Social Science / Popular Culture; Social Science / Women's Studies; Technology & Engineering / General

The Expansion of Punk Rock: Riot Grrrl Challenges to Gender Power Relations in British Indie Music Subcultures - DOWNES, JULIA (Women's Studies, 2012)
Publisher: Routledge _eprint: https://doi.org/10.1080/00497878.2012.636572

'Rock On': Women, ageing and popular music - Jennings, R.; Gardner, Abigail ('Rock On': Women, Ageing and Popular Music, 2012)
For female pop stars, whose star bodies and star performances are undisputedly the objects of a sexualized external gaze, the process of ageing in public poses particular challenges. Taking a broadly feminist perspective, 'Rock On': women, ageing and popular music shifts popular music studies in a new direction. Focussing on British, American and Latina women performers and ageing, the collection investigates the cultural work performed by artists such as Shirley Bassey, Petula Clark, Madonna, Celia Cruz, Grace Jones and Courtney Love. The study crosses generations of performers and audiences enabling an examination of changing socio-historical contexts and an exploration of the relationships at play between performance strategies, star persona and the popular music press. For instance, the strategies employed by Madonna and Grace Jones to engage with the processes and issues related to public ageing are not the same as those employed by Courtney Love or Celia Cruz. The essays in this insightful collection reflect on the ways that artists and fans destabilise both the linear trajectories and the compelling weight of expectations regarding ageing by employing different modalities of resistance through persona re-invention, nostalgia, postmodern intertextuality and even early death as the ultimate denial of age.

The Lost Women of Rock Music: Female Musicians of the Punk Era - Reddington, Helen (Equinox Pub., 2012)
In the late 1970s and early 1980s a new phenomenon emerged in UK popular music - female guitarists, bass-players, keyboard-players and drummers began playing in bands. Before this time, women's presence in rock bands, with a few notable exceptions, had always been as vocalists. This sudden influx of female musicians into the male domain of rock music was brought about by the enabling ethic of punk rock ('anybody can do it ') and by the impact of the Sex Discrimination Act. With the demise of the punk scene, interest in these musicians evaporated and other priorities became important to music audiences. This book investigates the social and commercial reasons why these women became lost from the rock music record, and rewrites this period of popular music history. In addition to a wealth of original interview material with key protagonists, including the late John Peel, Geoff Travis, The Raincoats and Poison Girls, this new edition has been updated to include interviews with members of Birmingham-based band The Au Pairs, Leeds-based band Delta 5 and Viv Albertine of The Slits. Lucy Whitman (aka Lucy Toothpaste), who started the fanzine Jolt and later wrote for Spare Rib, also provides enlightening words on the relationship between female punk band members and feminism. The author also draws on her own experience as bass-player in a punk band.
Google-Books-ID: blSWuAAACAAJ
Keywords: Music / Genres & Styles / Punk; Music / History & Criticism; Social Science / Women's Studies